Passato e presente all’edificio Garbasso: il decimo anniversario del GGI e la mostra “La fisica ad Arcetri” - Dominici, Daniele (Il Colle di Galileo, 2016)
A conference was held at Arcetri to mark the tenth anniversary of the Galileo Galilei Institute for Theoretical Physics. The event was attended by the President of the National Institute for Nuclear Physics and the "Rettore" of the University of Florence. To mark the anniversary, an exhibition was organised “La Fisica ad Arcetri. Dalla nascita della Regia Università alle leggi razziali” (Physics at Arcetri. From the Creation of the Royal University to the Racial Laws), opened on 24 May in the Exhibition Hall of the Historic Archives of Florence (Via dell’Oriuolo 35, Florence) running up to 30 September.